2015
DOI: 10.1155/2015/231070
|View full text |Cite
|
Sign up to set email alerts
|

High Grade (Large Cell) Neuroendocrine Carcinoma of the Nasopharynx: Novel Case Report with Touch Preparation Cytology and Positive EBV Encoded Early RNA

Abstract: Fewer than five case reports of primary large cell neuroendocrine carcinoma of the nasopharynx are known to the authors. No previous reports have included examples of cytomorphology or have proven association with Epstein-Barr virus. We herein illustrate MRI findings, histopathologic features, immunohistochemical characterization, cytologic details, and in situ hybridization studies from a unique case of primary large cell neuroendocrine carcinoma of the nasopharynx in a 38-year-old Caucasian male patient. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…5 This particular study did not examine the EBV status of the neuroendocrine carcinomas with MSI. 6 The three cases described herein belong to this unique subtype of pure LCNEC. Despite showing lymphovascular invasion and lymph node spread, the three patients that we document had longer survival periods than the average survival periods associated with LCNEC.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…5 This particular study did not examine the EBV status of the neuroendocrine carcinomas with MSI. 6 The three cases described herein belong to this unique subtype of pure LCNEC. Despite showing lymphovascular invasion and lymph node spread, the three patients that we document had longer survival periods than the average survival periods associated with LCNEC.…”
Section: Discussionmentioning
confidence: 83%
“…In a follow‐up study, the neuroendocrine carcinomas with MSI (including six LCNECs) also showed BRAF mutations . This particular study did not examine the EBV status of the neuroendocrine carcinomas with MSI …”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The 2017 World Health Organization criteria and classification system for neuroendocrine tumors of head and neck regions was modified so that LCNEC is classified as poorly differentiated neuroendocrine carcinoma, a new disease entity separate from atypical carcinoid. 9 We report a case of LCNEC arising from the maxillary sinus, for which the preoperative cytological diagnosis was difficult, and discuss the diagnostic pitfalls and difficulties in differential diagnosis between 9 We report a case of LCNEC arising from the maxillary sinus, for which the preoperative cytological diagnosis was difficult, and discuss the diagnostic pitfalls and difficulties in differential diagnosis between …”
Section: Introductionmentioning
confidence: 99%
“…9 We report a case of LCNEC arising from the maxillary sinus, for which the preoperative cytological diagnosis was difficult, and discuss the diagnostic pitfalls and difficulties in differential diagnosis between LCNEC and other head and neck lesions with similar cytological findings.A 60-year-old man with right-sided face pain presented with swelling at the right cheek, and complained of right nasal obstruction and lacrimation. We report a case of LCNEC causing difficulty in cytological diagnosis.…”
mentioning
confidence: 97%
See 1 more Smart Citation